Extensive amplification of GI-VII-6, a multidrug resistance genomic island of Salmonella enterica serovar Typhimurium, increases resistance to extended-spectrum cephalosporins - Lee, Ken-ichi; Kusumoto, Masahiro; Sekizuka, Tsuyoshi; Kuroda, Makoto; Uchida, Ikuo; Iwata, Taketoshi; Okamoto, Susumu; Yabe, Kimiko; Inaoka, Takashi; Akiba, Masato (Frontiers in Microbiology, 2015)
GI-VII-6 is a chromosomally integrated multidrug resistance genomic island harbored by a specific clone of Salmonella enterica serovar Typhimurium (S. Typhimurium). It contains a gene encoding CMY-2 β-lactamase (blaCMY-2), and therefore contributes to extended-spectrum cephalosporin resistance. To elucidate the significance of GI-VII-6 on adaptive evolution, spontaneous mutants of S. Typhimurium strain L-3553 were selected on plates containing cefotaxime (CTX). The concentrations of CTX were higher than its minimum inhibition concentration to the parent strain. The mutants appeared on the plates containing 12.5 and 25 μg/ml CTX at a frequency of 10−6 and 10−8, respectively. No colonies were observed at higher CTX concentrations. The copy number of blaCMY-2 increased up to 85 per genome in the mutants, while the parent strain contains one copy of that in the chromosome. This elevation was accompanied by increased amount of transcription. The blaCMY-2 copy number in the mutants drastically decreased in the absence of antibiotic selection pressure. Southern hybridization analysis and short-read mapping indicated that the entire 125 kb GI-VII-6 or parts of it were tandemly amplified. GI-VII-6 amplification occurred at its original position, although it also transposed to other locations in the genome in some mutants, including an endogenous plasmid in some of the mutants, leading to the amplification of GI-VII-6 at different loci. Insertion sequences were observed at the junction of the amplified regions in the mutants, suggesting their significant roles in the transposition and amplification. Plasmid copy number in the selected mutants was 1.4 to 4.4 times higher than that of the parent strain. These data suggest that transposition and amplification of the blaCMY-2-containing region, along with the copy number variation of the plasmid, contributed to the extensive amplification of blaCMY-2 and increased resistance to CTX.